Metabolism of Glycolate in Isolated Spinach Leaf Peroxisomes : KINETICS OF GLYOXYLATE, OXALATE, CARBON DIOXIDE, AND GLYCINE FORMATION - Chang, Chi-Cheng (1981)
The flow of glyoxylate derived from glycolate into various metabolic routes in the peroxisomes during photorespiration was assessed. Isolated spinach leaf peroxisomes were fed [(14)C] glycolate in the absence or presence of exogenous glutamate, and the formation of radioactive glyoxylate, CO(2), glycine, oxalate, and formate was monitored at time intervals. In the absence of glutamate, 80% of the glycolate was consumed within 2 hours and concomitantly glyoxylate accumulated; CO(2), oxalate, and formate each accounted for less than 5% of the consumed glycolate. In the presence of equal concentration of glutamate, glycolate was metabolized at a similar rate, and glycine together with some glyoxylate accumulated; CO(2), oxalate, and formate each accounted for an even lesser percentage of the consumed glycolate. CO(2) and oxalate were not produced in significant amounts even in the absence of glutamate, unless glycolate had been consumed completely and glyoxylate had accumulated for a prolonged period. These in vitro findings are discussed in relation to the extent of CO(2) and oxalate generated in leaf peroxisomes during photorespiration.